2019
DOI: 10.1089/neu.2018.5766
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response Mediates Cardiac Dysfunction after Traumatic Brain Injury

Abstract: Cardiovascular complications are common after traumatic brain injury (TBI) and are associated with increased morbidity and mortality. In this study, we investigated the possible role of the immune system in mediating cardiac dysfunction post-TBI in mice. Adult male C57BL/6J mice were subjected to a TBI model of controlled cortical impact (CCI) with or without splenectomy (n = 20/group). Splenectomy was performed immediately prior to induction of TBI. Cardiac function was measured using echocardiography prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…ICAM-1 and MCP-1 can be induced by the pro-inflammation molecules interleukin-1 (IL-1) and TNF. Our pre-clinical studies also found that ischemic stroke and TBI in mice significantly increase serum and heart ICAM-1 and MCP-1 expression as well as induce heart deficits ( 5 , 10 ). In the present study, we found that ICH significantly increases ICAM-1, MCP-1 and IL-1 expression in the heart and serum as well as increases inflammatory cells (leukocyte and macrophage) infiltration into the heart after ICH.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…ICAM-1 and MCP-1 can be induced by the pro-inflammation molecules interleukin-1 (IL-1) and TNF. Our pre-clinical studies also found that ischemic stroke and TBI in mice significantly increase serum and heart ICAM-1 and MCP-1 expression as well as induce heart deficits ( 5 , 10 ). In the present study, we found that ICH significantly increases ICAM-1, MCP-1 and IL-1 expression in the heart and serum as well as increases inflammatory cells (leukocyte and macrophage) infiltration into the heart after ICH.…”
Section: Discussionsupporting
confidence: 65%
“…Mortality rates associated with ICH are as high as 35–52% within the first 30 days after ICH and approximately 42–65% over the first year following ICH ( 1 ). Cardiac dysfunction occurs commonly in patients and experimental animals with stroke and traumatic brain injury (TBI) ( 3 5 ). Cardiovascular complications in ICH patients are closely related with early mortality and poor outcome after ICH ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mild TBI enhances liver inflammatory markers by altering the redox homeostasis and given their wide implications for their interaction between brain and body, leakage of pro-inflammatory factors through the disrupted BBB can exacerbate brain injury pathology [242][243][244]. TBI can promote cardiovascular risk factors through increase in expression of pro-inflammatory chemokines and apoptosis [245,246]. The spleen is an important lymphoid organ innervated by sympathetic nerve fibers that are in contact with splenic immune cells to create a neuroimmune link [247].…”
Section: Other Organsmentioning
confidence: 99%
“…In agreement with this idea, mice subjected to splenectomy after controlled cortical impact (CCI) showed significantly improved cardiac function, and decreased cardiac fibrosis, oxidative stress, cardiomyocyte apoptosis, and decreased infiltration of immune cells and inflammatory factors to the heart. (Zhao et al, 2019). Considering that systemic inflammatory response syndrome in TBI patients is associated with systolic cardiac dysfunction (Deepika et al, 2018) (Hasen et al, 2019), it is plausible that a paroxysmal sympathetic hyperactivity followed by immune response after brain injury may play a vital role in mediating brain-heart interaction.…”
Section: Tbi and Cardiovascular/heart Interaction Between Brain And Bodymentioning
confidence: 99%